Green tea and exercise interventions as nondrug remedies in geriatric patients with rheumatoid arthritis - Alghadir, Ahmad H. (J Phys Ther Sci, 2016)
This study aimed to evaluate the effects of green tea and supervised exercise training interventions on improvement of disease activity and bone metabolism markers in rheumatoid arthritis patients. [Subjects and Methods] One-hundred and twenty subjects who had a mean age of (60.7 ± 2.53 years) and had been diagnosed with rheumatoid arthritis at least ten years previously were randomly included in this study. Patients were treated with infliximab, green tea, or a supervised exercise program for six months. Disease activity markers as well as antioxidant activity of green tea extracts were estimated before supplementation using in vitro assays. [Results] Rheumatoid arthritis patients treated with green tea for 6 months alone or in combination with infliximab or an exercise program showed significant improvement in disease activity parameters, including C-reactive protein, and erythrocyte sedimentation rate, swollen and tender joints counts, and modified Stanford Health Assessment Questionnaire score, along with an increase in serum levels of bone resorption markers, i.e., deoxypyridinoline, amino-terminal telopeptide of type 1 collagen, and bone alkaline phosphatase, at 6 months of after initial treatment. The European League Against Rheumatism and American College of Rheumatology scores revealed more clinical improvement in the disease activity of rheumatoid arthritis patients treated with green tea along with exercise compared with rheumatoid arthritis patients treated with infliximab or exercise combinations. This may have been due to the higher potential antioxidant activity of green tea (89.6% to 96.5%). [Conclusion] Both exercise and green tea interventions appeared to be beneficial as nondrug modulates for rheumatoid arthritis disorders.